A RARE CASE OF STERILE ENDOPHTHALMITIS FOLLOWING INTRAVITREAL TRIAMCINOLONE ACETONIDE INJECTION IN VITRECTOMIZED EYE: Poster Presentation - Case Report - Resident - Pitanatri, Nyoman Brahmani; Panjawati, Ni Luh Diah (Majalah Oftalmologi Indonesia, 2023)
Introduction : Intravitreal Triamcinolone Acetonide (IVTA) has been widely used to treat Diabetic Macular Edema (DME). Sterile endophthalmitis is one of the major related complications after IVTA which occurs between 0.20% and 6.73% of the injections. We present a case of sterile endophthalmitis following IVTA injection in a patient with a vitrectomized eye and DME. Case Illustration : A 53?year?old female patient with a history of vitrectomy due to high-risk characteristic proliferative diabetic retinopathy on her right eye underwent IVTA for DME. One day after the injection, the visual acuity (VA) improved from 6/45 to 6/12 without any complication. Three days later, she complained of ocular discomfort and sudden diminution of vision. The VA had dropped to hand movement, with conjunctival injection, hypopyon, anterior chamber reaction, and an inaccessible fundus. The patient was treated with topical antibiotics, corticosteroids, and cycloplegic, followed by intravitreal antibiotics injection. Furthermore, vitrectomy and vitreous tap were performed. On one- week follow-up, the VA was improved to 6/60 with normal IOP. The anterior chamber and the vitreous cavity remained clear. Discussion : The etiology of sterile endophthalmitis following IVTA injection remains unclear. Compared to infectious endophthalmitis, the patient is usually in less pain, and the eye is less injected. Although it generally has a benign course, some studies have shown serious complications such as vitreous hemorrhage and retinal detachment. Therefore, caution should be taken to prevent such complications from developing. Conclusion : In presumed sterile endophthalmitis, a careful diagnosis and intervention must be reconsidered to avoid potential long-term visual loss due to its related complications.